Effectiveness of Wudhu to Reducing Anxiety During Competency Test on Students - Fatoni, Fatoni; Sumartini, Rina; Mulyat, Mulyati; Jamaludin, Jamaludin (KnE Social Sciences, 2023)
Anxiety is an emotional response to individuals perspective thas was subjective and an unknown cause. National competency exams anxiety is one of psychological problems that nursing students often experience that is a fear of failure, getting bad grades, or cannot get through the exams. Therefore, there is a need to minimize anxiety. The treatment of anxiety can be with nonpharmacological therapy. One of the nonpharmacological therapy using hydotheraphy with wudu’ technique. This research aims to identify the effect of wudu’ on changes toward anxiety for nursing students in the national competency exam. The research design used in this research is preexperiment with single group design, pre- and post-test design. The research samples in this research were 24 respondents with simple random sampling technique. Instrument used in this research is Visual Analog Scale for Anxiety (VAS-A). Statistical test was doneusing wilcoxon signed-rank test, the obtained p-value = 0.000 (< 0.05), showed the influence of wudu’ on changes of anxiety for Universitas Faletehan nursing students anxiety in the national competency examination. Wudu’ contains elements of relaxation to reduce anxiety and provides benefits for physical, psyclogical, and emotional control. The results of this research can be used as a reference of nonpharmacological therapy to treat anxiety in national competency examination. Keywords: anxiety, national competency test, wudhu’